Vertical patterns of ichthyoplankton at the interface between a temperate estuary and adjacent coastal waters: Seasonal relation to diel and tidal cycles - Primo, Ana Lígia (2012)
Vertical distribution and migration pattern of ichthyoplankton assemblage in the Mondego estuary were investigated in relation to diel and tidal cycle. Summer and winter communities were sampled, at surface and bottom, over a diel cycle during spring and neap tides at a fixed station at the mouth of the estuary. Summer presented higher larvae density mainly of Pomatoschistus spp., Gobius niger and Parablennius pilicornis. Main species in winter assemblages were Pomatoschistus spp. and Sardina pilchardus. There were no differences between depth stratums across diel or tide cycle. Nevertheless, main species larval densities showed significant periodic variation associated with tide (M2) and diel (K1) cycles presenting generally, higher density at night and around low tide. Conversely, vertical patterns observed could not be related with diel or tidal cycle. Tough, main species presented some extent of vertical migration. Vertical patterns observed appear to be related to seasonal stratification and river flow, increasing amplitude during periods of less stratification and lower water currents. Present study provides a better understanding of ichthyoplankton vertical movement patterns and of small scale dynamics at the interface of two coastal European systems.